Tuning the Kingdom: Kawuugulu Musical Performance, Politics, and Story Telling in Buganda. Damascus Kafumbe, 2018. Rochester: University of Rochester Press. 31 illustrations, 23 musical examples, bibliography, index. 151 pp. - Njoku, Obianuju Akunna (International Library of African Music, 2022)
pages: 138-141
Keywords: Storytelling; Music; Politics; Buganda Kingdom; Uganda; Kawuugulu; Musical Performance; African Music